The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.bios.2015.10.061
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondria-targeted ratiometric two-photon fluorescent probe for biological zinc ions detection

Abstract: A mitochondria-targeted ratiometric two-photon fluorescent probe (Mito-MPVQ) for biological zinc ions detection was developed based on quinolone platform. Mito-MPVQ showed large red shifts (68nm) and selective ratiometric signal upon Zn2+ binding. The ratio of emission intensity (I488 nm/I420 nm) increases dramatically from 0.45 to 3.79 (ca. 8-fold). NMR titration and theoretical calculation confirmed the binding of Mito-MPVQ and Zn2+. Mito-MPVQ also exhibited large two-photon absorption cross sections (150GM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…However, there is no consistent conclusion about the subcellular localization of supplementary Zinc in the cells. Some studies suggested that Zinc targeted in mitochondria [43,44], while other researches advocated that Zinc could trigger apoptosis by accumulating Zinc into the lysosome [45,46]. In our study, in accordance, we observed that ZPT transported Zinc mostly into lysosomes, accumulated Zinc could cause the lysosomal membrane permeabilization (LMP) and consequent cathepsin D distribution.…”
Section: Discussionsupporting
confidence: 88%
“…However, there is no consistent conclusion about the subcellular localization of supplementary Zinc in the cells. Some studies suggested that Zinc targeted in mitochondria [43,44], while other researches advocated that Zinc could trigger apoptosis by accumulating Zinc into the lysosome [45,46]. In our study, in accordance, we observed that ZPT transported Zinc mostly into lysosomes, accumulated Zinc could cause the lysosomal membrane permeabilization (LMP) and consequent cathepsin D distribution.…”
Section: Discussionsupporting
confidence: 88%
“…9–11 For example, a mitochondrial probe QBMP synthesized with a favorable 2PA cross-section (70.5 GM) achieved a tissue penetration depth of 225 μm in in vivo bioimaging. 9–11 However, these mitochondrial probes still suffer from low two-photon absorption properties 11–13 or poor biocompatibility, 14,15 restricting their application in live animal bioimaging. This study developed a water-soluble probe with low cytotoxicity and a relatively high 2PA cross-section of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Representative examples are shown in Figure 9. [70][71][72][73] MPVQ-series, initially developed at Meng's group, 73 consisted of BPA-appended quinoline as fluorescent skeleton with a conjugated donor on the 6-position, whereas chromis-1 contains a 2-arylthiazol as a push-pull fluorophore. In all cases, a red-shifted fluorescence was observed in presence of Zn 2+ , which was accompanied by an increased TPA cross-section.…”
Section: Ict-based Sensorsmentioning
confidence: 99%